Global convergence analysis for the NIC flow - Liu, Wanquan; Yan, Wei-Yong; Sreeram, V.; Teo, Kok (Institute of Electrical and Electronics Engineers (IEEE), 2001)
Previously, a family of fast subspace tracking algorithms based on a novel information criterion (NIC) has been proposed and investigated. It is known that these new algorithms are associated with a new kind of flow, which is called the NIC flow in this paper as in the case of the conventional Oja subspace algorithms with the Oja flow. In this paper, some fundamental questions about this new NIC flow such as its solution existence and convergence, are investigated. In addition, the convergence domain is characterized. Some important results on these issues are obtained via manifold theory